A Analisis Cemaran Bakteri Coliform Dan Identifikasi Bakteri Escherichia Coli Pada Air Galon Di Desa Sungai Danau: Analisis Cemaran Bakteri Coliform Dan Identifikasi Bakteri Escherichia Coli Pada Air Galon Di Desa Sungai Danau - Taufik Kurahman; Rohama Rohama; Rina Saputri (LPPM Universitas Sari Mulia, 2022)
Currently, the use of refill drinking water depots (DAMIU) is relatively higher, so that the use of DAMIU must pay attention to sanitation and hygiene to support DAMIU to avoid contamination with Coliform bacteria, one example of Coliform bacteria is Escherichia Coli bacteria. Escherichia coli bacteria is one of the causes of diarrheal disease. Diarrhea is an endemic disease with the potential for extraordinary events (KLB) which often leads to death in Indonesia. The prevalence of diarrhea in Indonesia is 6.8% or 1,017,290 people and it is known that Tanah Bumbu district is the third largest contributor to diarrhea, which is 4.3% or as many as 2006 people in South Kalimantan, so it is necessary to test DAMIU in Sungai Danau Village. using the MPN method.